null

Geometric Algebra

Session 7: Reflections &
Rotations

Cyberworlds 2009 © John Vince

Rotations & Reflections




2D Reflection
3D Reflection
Reflecting in a mirror
Rotating by reflecting
Rotors

Cyberworlds 2009 © John Vince

e
2
öa
α
′m
αα e1
2D Reflection

a = α1ε1 + α2 ε 2
α′ = − α1ε1 + α2 ε 2
Cyberworlds 2009 © John Vince

e
2
öa
α
′m
αα e1

2D Reflection
a = α1ε1 + α2 ε 2
α′ = − α1ε1 + α2 ε 2

We need to preserve the sign of
the component of a parallel to m,
but flip the sign of the component
of a perpendicular to m.
Cyberworlds 2009 © John Vince

ö
m
P a
a′ a
a
a
P
a
^
2D Reflection

a′ = aP + a ^

ö ×a ) m
ö
aP = ( m
ö (a Ù m
ö) = - m
ö (m
ö Ùa ) = ( m
ö Ùa ) m
ö WHY?
a^ = m
Cyberworlds 2009 © John Vince

WHY?
ö ( a ∧ µ ) ροτατεσµ
m

90° αντιχλοχκωισε

Cyberworlds 2009 © John Vince

WHY?
ö ( a ∧ µ ) ροτατεσµ
m

90° αντιχλοχκωισε

( α∧ µ ) µ

90° χλοχκωισε

ροτατεσµ

Cyberworlds 2009 © John Vince

WHY?
ö ( a ∧ µ ) ροτατεσµ
m

90° αντιχλοχκωισε

( α∧ µ ) µ ροτατεσµ 90° χλοχκωισε
∴ µ ( α∧ µ ) = − ( α∧ µ ) µ = ( µ ∧ α) µ

Cyberworlds 2009 © John Vince

2D Reflection
a′ = aP + a ^
ö ×a ) m
ö
aP = ( m
ö Ùa ) m
ö
a^ = (m

Cyberworlds 2009 © John Vince

2D Reflection
a′ = aP + a ^
ö ×a ) m
ö
aP = ( m
ö Ùa ) m
ö
a^ = (m
ö ×a ) m
ö + (m
ö Ùa ) m
ö
a ¢= ( m

Cyberworlds 2009 © John Vince

2D Reflection
a′ = aP + a ^
ö ×a ) m
ö
aP = ( m
ö Ùa ) m
ö
a^ = (m
ö ×a ) m
ö + (m
ö Ùa ) m
ö
a ¢= ( m
ö m
ö
a¢= ma

Cyberworlds 2009 © John Vince

e
2
α
′ µ
 a
e3 e1
3D Reflection

Cyberworlds 2009 © John Vince

e
2
α
′ µ
 a
e3 e1

3D Reflection
a = ε1 + ε 2 − ε 3

Cyberworlds 2009 © John Vince

e
2
α
′ µ
 a
e3 e1

3D Reflection
a = ε1 + ε 2 − ε 3
α′ = µ αµ

Cyberworlds 2009 © John Vince

e
2
α
′ µ
 a
e3 e1

3D Reflection
a = ε1 + ε 2 − ε 3
α′ = µ αµ
α′ = ε 2 ( ε1 + ε 2 − ε 3 ) ε 2

Cyberworlds 2009 © John Vince

e
2
α
′ µ
 a
e3 e1

3D Reflection
a = ε1 + ε 2 − ε 3
α′ = µ αµ
α′ = ε 2 ( ε1 + ε 2 − ε 3 ) ε 2
α′ = ε 212 + ε 222 − ε 232

Cyberworlds 2009 © John Vince

e
2
α
′ µ
 a
e3 e1

3D Reflection
a = ε1 + ε 2 − ε 3
α′ = µ αµ
α′ = ε 2 ( ε1 + ε 2 − ε 3 ) ε 2
α′ = ε 212 + ε 222 − ε 232
α′ = −ε1 + ε 2 + ε 3
Cyberworlds 2009 © John Vince

3D Reflections



Reflect vectors mVm
Reflect bivectors mBm
Reflect trivectors mTm
Where m is a unit vector

Cyberworlds 2009 © John Vince

a
a
P
a
P
a
µ
^

a
P

Reflecting in a Mirror

Cyberworlds 2009 © John Vince

a
a
P
a
P
a
µ
^

a
P

Reflecting in a Mirror
aP = ( µ ⋅ α) µ
α⊥ = ( α∧ µ ) µ = − ( µ ∧ α) µ
α′ = −αΠ + α⊥
α′ = − ( µ ⋅ α) µ − ( µ ∧ α) µ
α′ = − µ αµ

Cyberworlds 2009 © John Vince

Mirror Reflections



Reflect vectors -mVm
Reflect bivectors mBm
Reflect trivectors -mTm
Where m is a unit vector

Cyberworlds 2009 © John Vince

N θP
M
R
θ

α
α
P
¢q-aOαP
Rotating by Reflecting

Cyberworlds 2009 © John Vince

ö
n
NθpP
RM
ö
m
R
P
¢p¢OpP

Rotating by Reflecting

Cyberworlds 2009 © John Vince

ö
n
NθpP
RM
ö
m
R
P
¢p¢OpP

Rotating by Reflecting

p R = − µ πµ
 Ρ ν = ν µ πµ ν
π ′ = − νπ

Cyberworlds 2009 © John Vince

ö
n
NθpP
RM
ö
m
R
P
¢p¢OpP

Rotating by Reflecting

ö m
ö nö
p′ = nömp
ö and n)
ö
(but is rotated twice the angle between m
Cyberworlds 2009 © John Vince

e

ö
n
Π
′π′ m
ö
e
1
Μ
pP
2D Example

Cyberworlds 2009 © John Vince

e

ö
n
Π
′π′ m
ö
e
1
Μ
pP

Example
ö = ε2
m
ν = −ε1
π = ε1 − ε 2

Cyberworlds 2009 © John Vince

e

ö
n
Π
′π′ m
ö
e
1
Μ
pP

2D Example
ö = ε2
m
ν = −ε1
π = ε1 − ε 2
π ′ = ν µ πµ ν

Cyberworlds 2009 © John Vince

e

ö
n
Π
′π′ m
ö
e
1
Μ
pP

2D Example
ö = ε2
m
ν = −ε1
π = ε1 − ε 2
π ′ = ν µ πµ ν
π ′ = −ε1ε 2 ( ε1 − ε 2 ) ε 2 ( −ε1 )

Cyberworlds 2009 © John Vince

e

ö
n
Π
′π′ m
ö
e
1
Μ
pP

2D Example
ö = ε2
m
ν = −ε1
π = ε1 − ε 2
π ′ = ν µ πµ ν
π ′ = −ε1ε 2 ( ε1 − ε 2 ) ε 2 ( −ε1 )
π ′ = ε12121 − ε12221
Cyberworlds 2009 © John Vince

e

ö
n
Π
′π′ m
ö
e
1
Μ
pP

2D Example
ö = ε2
m
ν = −ε1
π = ε1 − ε 2
π ′ = ν µ πµ ν
π ′ = −ε1ε 2 ( ε1 − ε 2 ) ε 2 ( −ε1 )
π ′ = ε12121 − ε12221
π ′ = −ε1 + ε 2
Cyberworlds 2009 © John Vince

e
2
1
Π
′π′ν20°πP
µ

ν
6
0
°
µ
1
1
e3 e1
3D Example

Cyberworlds 2009 © John Vince

e
2
1
Π
′π′ν20°πP
µ

ν
6
0
°
e31 µ 1e1

3D Example
p = ε1 + ε 2
µ = ε1 − ε 3
µ =

1
2

( ε1 − ε 3 )

ν = ε2 − ε3
ν =

1
2

(ε2 − ε3 )

Cyberworlds 2009 © John Vince

e
2
1
Π
′π′ν20°πP
µ

ν
6
0
°
e31 µ 1e1

3D Example

ö=
m
ν =

1
2

1
2

( ε1 − ε 3 )

( ε2 − ε3 )

ν µ =

1
2

(ε2 − ε3 )

1
2

( ε1 − ε 3 ) = 12 ( ε 21 − ε 23 − ε 31 + 1)

µ ν =

1
2

( ε1 − ε 3 )

1
2

( ε 2 − ε 3 ) = 12 ( −ε 21 + ε 23 + ε 31 + 1)

Cyberworlds 2009 © John Vince

e
2
1
Π
′π′ν20°πP
µ

ν
6
0
°
e31 µ 1e1

3D Example

ö m
ö nö
p′ = nömp
p¢= 12 ( e 21 - e 23 - e 31 + 1) ( e1 + e 2 ) 12 ( - e 21 + e 23 + e 31 + 1)
p¢= e 2 + e 3

Cyberworlds 2009 © John Vince

Rotors
ö ∧ ν ωιτη ανγλε θ
Bivector defining the plane is m
π ′ = ν µ πµ ν

Cyberworlds 2009 © John Vince

Rotors
ö ∧ ν ωιτη ανγλε θ
Bivector defining the plane is m
π ′ = ν µ πµ ν
Λετ Ρ = ν µ

ανδ Ρ = µ ν

π ′ = Ρ πΡ

Cyberworlds 2009 © John Vince

Rotors
ö ∧ ν ωιτη ανγλε θ
Bivector defining the plane is m
π ′ = ν µ πµ ν
Λετ Ρ = ν µ

ανδ Ρ = µ ν

π ′ = Ρ πΡ
ν µ = ν ⋅ µ − µ ∧ ν

Cyberworlds 2009 © John Vince

Rotors
ö ∧ ν ωιτη ανγλε θ
Bivector defining the plane is m
π ′ = ν µ πµ ν
Λετ Ρ = ν µ

ανδ Ρ = µ ν

π ′ = Ρ πΡ
ν µ = ν ⋅ µ − µ ∧ ν
µ ν = ν ⋅ µ + µ ∧ ν

Cyberworlds 2009 © John Vince

Rotors
ö ∧ ν ωιτη ανγλε θ
Bivector defining the plane is m
π ′ = ν µ πµ ν
Λετ Ρ = ν µ

ανδ Ρ = µ ν

π ′ = Ρ πΡ
ν µ = ν ⋅ µ − µ ∧ ν
µ ν = ν ⋅ µ + µ ∧ ν
ν ⋅ µ = χοσθ

Cyberworlds 2009 © John Vince

Rotors
ö ∧ ν ωιτη ανγλε θ
Bivector defining the plane is m
π ′ = ν µ πµ ν
Λετ Ρ = ν µ

ανδ Ρ = µ ν

π ′ = Ρ πΡ
ν µ = ν ⋅ µ − µ ∧ ν
µ ν = ν ⋅ µ + µ ∧ ν
ν ⋅ µ = χοσθ
 ινθ
µ ∧ ν = Βσ

Cyberworlds 2009 © John Vince

Rotors
ö ∧ ν ωιτη ανγλε θ
Bivector defining the plane is m
π ′ = ν µ πµ ν
Λετ Ρ = ν µ

ανδ Ρ = µ ν

π ′ = Ρ πΡ
ν µ = ν ⋅ µ − µ ∧ ν
µ ν = ν ⋅ µ + µ ∧ ν
ν ⋅ µ = χοσθ
 ινθ
µ ∧ ν = Βσ
 ινθ
Ρ = χοσθ − Βσ
 ινθ
Ρ = χοσθ + Βσ
Cyberworlds 2009 © John Vince

Rotors
 ινθ
R = χοσθ − Βσ
 ινθ
Ρ = χοσθ + Βσ

Cyberworlds 2009 © John Vince

Rotors
 ινθ
R = χοσθ − Βσ
 ινθ
Ρ = χοσθ + Βσ
π ′ = Ρ πΡ

Cyberworlds 2009 © John Vince

Rotors
 ινθ
R = χοσθ − Βσ
 ινθ
Ρ = χοσθ + Βσ
π ′ = Ρ πΡ
 ινθ ) π ( χοσθ + Βσ
 ινθ )
π ′ = ( χοσθ − Βσ
[ ροτατεσπ τηρουγη ανδ ανγλε 2θ ]

Cyberworlds 2009 © John Vince

Rotors
 ινθ
R = χοσθ − Βσ
 ινθ
Ρ = χοσθ + Βσ
π ′ = Ρ πΡ
 ινθ ) π ( χοσθ + Βσ
 ινθ )
π ′ = ( χοσθ − Βσ
[ ροτατεσπ τηρουγη ανδ ανγλε 2θ ]
 ιν (θ 2 )) π ( χοσ(θ 2 ) + Βσ
 ιν (θ 2 ))
π ′ = ( χοσ(θ 2 ) − Βσ

Cyberworlds 2009 © John Vince

Rotors
 ινθ
R = χοσθ − Βσ
 ινθ
Ρ = χοσθ + Βσ
π ′ = Ρ πΡ
 ινθ ) π ( χοσθ + Βσ
 ινθ )
π ′ = ( χοσθ − Βσ
[ ροτατεσπ τηρουγη ανδ ανγλε 2θ ]
 ιν (θ 2 )) π ( χοσ(θ 2 ) + Βσ
 ιν (θ 2 ))
π ′ = ( χοσ(θ 2 ) − Βσ
π ′ = ( χοσ(θ 2 ) − Ιασιν (θ 2 )) π ( χοσ(θ 2 ) + Ιασιν (θ 2 ))

Cyberworlds 2009 © John Vince

ea2 π′p90°
ö
B
e3 e1
Rotor Example

Cyberworlds 2009 © John Vince

ea2 π′p90°
ö
B
e3 e1

Rotor Example
α = 90°
a = e2
p = e1 + e 2
ö = Ia = e e = e
B
123 2
31
p¢= ( cos 45° - e 31 sin 45° ) ( e1 + e 2 ) ( cos 45° + e 31 sin 45° )
æ 2
æ 2
2 ö
2 ö
p¢= ç
e 31 ÷( e1 + e 2 ) ç
+
e 31 ÷
2
2
è 2
ø
è 2
ø
p¢= e 2 - e 3

Cyberworlds 2009 © John Vince

e
2
π′ p
ö
B
e3 a e1

Rotor Example (reverse)
α = 90°
a = - e2
p = e1 + e 2
ö = Ia = - e e = - e
B
123 2
31
p¢= ( cos 45° + e 31 sin 45° ) ( e1 + e 2 ) ( cos 45° - e 31 sin 45° )
æ 2
æ 2
2 ö
2 ö
p¢= ç
+
e 31 ÷( e1 + e 2 ) ç
e 31 ÷
2
2
è 2
ø
è 2
ø
p¢= e 2 + e 3

Cyberworlds 2009 © John Vince

Rotor Matrix

ö = µ 1ε1 + µ 2 ε 2 + µ 3ε 3
m
ν = ν1ε1 + ν2 ε 2 + ν3ε 3

Cyberworlds 2009 © John Vince

Rotor Matrix

ö = µ 1ε1 + µ 2 ε 2 + µ 3ε 3
m
ν = ν1ε1 + ν2 ε 2 + ν3ε 3

Ρ = ν µ = ω + ξε 23 + ψε 31 + ζε12
Ρ = µ ν = ω − ξε 23 − ψε 31 − ζε12

ω2 + ξ2 + ψ2 + ζ2 = 1

Cyberworlds 2009 © John Vince

Rotor Matrix

ö = µ 1ε1 + µ 2 ε 2 + µ 3ε 3
m
ν = ν1ε1 + ν2 ε 2 + ν3ε 3
Ρ = ν µ = ω + ξε 23 + ψε 31 + ζε12

Ρ = µ ν = ω − ξε 23 − ψε 31 − ζε12

ω2 + ξ2 + ψ2 + ζ2 = 1
Λετ ϖ βε τηε ϖεχτορτο βε ροτατεδ
ϖ= ϖ1ε1 + ϖ2 ε 2 + ϖ3ε 3

Cyberworlds 2009 © John Vince

Rotor Matrix

ö = µ 1ε1 + µ 2 ε 2 + µ 3ε 3
m
ν = ν1ε1 + ν2 ε 2 + ν3ε 3
Ρ = ν µ = ω + ξε 23 + ψε 31 + ζε12

Ρ = µ ν = ω − ξε 23 − ψε 31 − ζε12

ω2 + ξ2 + ψ2 + ζ2 = 1
Λετ ϖ βε τηε ϖεχτορτο βε ροτατεδ
ϖ= ϖ1ε1 + ϖ2 ε 2 + ϖ3ε 3
ϖ′ = Ρ ( ϖ1ε1 + ϖ2 ε 2 + ϖ3ε 3 ) Ρ
ϖ′ = ( ω + ξε 23 + ψε 31 + ζε12 ) ( ϖ1ε1 + ϖ2 ε 2 + ϖ3ε 3 ) ( ω − ξε 23 − ψε 31 − ζε12 )

Cyberworlds 2009 © John Vince

Rotor Matrix

ö = µ 1ε1 + µ 2 ε 2 + µ 3ε 3
m
ν = ν1ε1 + ν2 ε 2 + ν3ε 3
Ρ = ν µ = ω + ξε 23 + ψε 31 + ζε12

Ρ = µ ν = ω − ξε 23 − ψε 31 − ζε12

ω2 + ξ2 + ψ2 + ζ2 = 1
Λετ ϖ βε τηε ϖεχτορτο βε ροτατεδ
ϖ= ϖ1ε1 + ϖ2 ε 2 + ϖ3ε 3
ϖ′ = Ρ ( ϖ1ε1 + ϖ2 ε 2 + ϖ3ε 3 ) Ρ
ϖ′ = ( ω + ξε 23 + ψε 31 + ζε12 ) ( ϖ1ε1 + ϖ2 ε 2 + ϖ3ε 3 ) ( ω − ξε 23 − ψε 31 − ζε12 )
ϖ′ = ????????
Cyberworlds 2009 © John Vince

Rotor Matrix
é1 - 2 ( y 2 + z 2 ) 2 ( xy - wz )
2 ( xz + wy ) ùé v1 ù
ê
úê ú
2
2
v ′ = ê 2 ( xy + wz ) 1 - 2 ( x + z ) 2 ( yz - wx ) úêv2 ú
ê
2
2 ú êv ú
2 ( yz + wx ) 1 - 2 ( x + y ) úûë 3 û
êë 2 ( xz - wy )

Cyberworlds 2009 © John Vince

The End
PHEW!

Cyberworlds 2009 © John Vince

Sign up to vote on this title
UsefulNot useful